Critical condition : health in Black America [videorecording (DVD)] / directed by Stanley Nelson. (PBS, 2025)
Black Americans are nearly twice as likely to have high blood pressure, diabetes, and heart disease than White Americans, and their life expectancy is about five years shorter. Why? In a special feature-length documentary, Oscar-nominated filmmaker Stanley Nelson investigates the dramatic health disparities in the US, even as scientists confirm that there are no meaningful genetic differences between races.